Comparison of intra-operative characteristics and early post-operative outcomes between endoscopic sinus surgery and balloon sinuplasty. (1st February 2017) - Koskinen, Anni; Mattila, Petri; Myller, Jyri; Penttilä, Matti; Silvola, Juha; Alastalo, Ismo; Huhtala, Heini; Hytönen, Maija; Toppila-Salmi, Sanna
Abstract: Conclusion: In terms of operation time, anesthesia method, and low complication rate, ESS and balloon sinuplasty seemed comparable. The advantages of balloon sinuplasty were shown to be shortness of sick leave, possibility to be performed as an in-office procedure, and lower adhesion formation. Background: Endoscopic sinus surgery (ESS) has been considered as a treatment of choice for persistent chronic rhinosinusitis (CRS). During the last decade balloon sinuplasty has been introduced as an alternative technique to dilate the ostium. Although balloon sinuplasty is considered relatively safe and efficient, comparative evidence of its putative intra-operative and post-operative advantages remain limited. Objectives: The aim of this retrospective controlled study was to evaluate intra-operative factors and early post-operative outcomes among CRS patients who had undergone maxillary sinus operation with either balloon sinuplasty or ESS technique. Materials and methods: Data were collected from 208 patients with CRS treated either with ESS or balloon sinuplasty during the years 2008–2010. Intra- and peri-operative factors were collected from patient records of the patients who met the inclusion criteria ( n  = 39 in ESS group and n  = 36 in balloon sinuplasty group). Results: There was no significant difference in operation time and anesthesia method between the two groups. No complications occurred with either technique. All ESS procedures and 67% of the balloon sinuplasty procedures were done in the hospital setting, whereas 33% of the balloon sinuplasty procedures were done in the office setting. The duration of sick leave and the number of patients with adhesions were significantly higher in the ESS group compared to the balloon sinuplasty group.